Update on New Species and Record of Fishes in the Coral Triangle Region for the Last 10 Years (2008-2019) - Fione Yukita Yalindua; Teguh Peristiwady; Putri Saphira Ibrahim (Journal of Tropical Biodiversity and Biotechnology, 2021)
Updated data is an essential requirement for carrying out research, planning, and policy briefs. The Coral reef triangle region is one of the areas with the highest diversity of marine biota and the discovery of new species in this area are increasing every year, much of this information is already available. However, most of the data is not available per region and is still scattered. This study aims to create a checklist and assessment of new species and a new record of fishes from this region over the last ten years based on several aspects, including species composition, pattern of distribution, endemicity, and depth using every source of the report and secondary literature data. The current new species and a new record of fish in the last decades combined consists of 360 species (268 new species and 92 new records). The most speciose group of family dominated by Gobiidae (93), followed by Labridae, Pomacentridae and Serranidae (18), Apogonidae (17), Dasyatidae (15), and the rest were ranged from 1-9 species per family. More than half of new species and new records are found in Indonesia, followed by the Philippines, Papua New Guinea, and Solomon Island. The result shows that cryptobenthic Families especially Gobiidae from genus Trimma and eviota are dominated the trend of new species and new record discovery and it is expected to rise over time while there will also be an emergence of some possibly new endemic species from major and rare families from the eastern part of Indonesia (West Papua and Papua New Guinea). Thus, the eastern part of Indonesia (Papua, Maluku, Aru Sea, and Papua New Guinea) and the northern part of Indonesia (North Sulawesi and Philippine) are suitable for exploration for marine biodiversity discovery research in the future.